PENINGKATAN KEMAMPUAN MENULIS TARUNA-TARUNI POLITEKNIK PERKERETAAPIAN INDONESIA MADIUN MELALUI KELAS LITERASI DI PERPUSTAKAAN - Dhina Setyo Oktaria; Sapto Priyanto; Armyta Puspitasari; Erifendi Churniawan; Ahmad Ependi; Atik R.R Siti Kuswati (Journal of Innovation Research and Knowledge, 2022)
This community service aims to provide understanding and improve the cadets' writing skills in the final project preparation because the cadets themselves do not fully understand the procedures for writing good scientific papers. The step used in achieving the goal is to provide materials for both theory and practice through online and offline literacy classes. The method used is blended learning strategy by combining face-to-face learning and information technology capabilities. Blended learning is more flexible to use during a pandemic because it is not limited by space and time so that the target of service can be achieved. The activity will be carried out for 4 (four) days with the distribution of materials according to the schedule that has been made. The cadets had been given a pre-test before learning began and a post-test after learning was completed to evaluate the success of this service activity. Pre-test result about the basic concept of scientific work obtained 52 results and post-test results obtained 70. Systematic materials and scientific writing techniques obtained pre-test results of 45.4 and post-test results of 67.4. The material for using digital literacy in writing works has a pre-test result of 39.4 and a post-test result of 63.2. For scientific publications, the results of the pre-test were 32.4 and the post-test results were 62.6. The results of the post-test for the four materials presented, the total average value was still below 62.82, this is still far below the standard average. The expected level is 80. The literacy class which is carried out by blended learning needs to be further improved based on data processing from google forms filled out by cadets with the results of the pre-test and post-test experiencing a significant increase from the four material themes presented.